STATE RESPONSIBILITY IN GUARANTEE TO FREEDOM OF RELIGION ACCORDING TO PERSPECTIVE OF HUMAN RIGHTS - Gary Gagarin Akbar, Muhammad; Guntara, Deny; Zuraida Supri, Ida (International Journal of Psychosocial Rehabilitation, 2020)
Guarantees regarding freedom of religion for Indonesian citizens have been included in Constitution of the Republic of Indonesia 1945. The Government of Indonesia has made various legal products in order to fulfill the right to freedom of religion and belief. In recent times, issues regarding in toleration related to religious freedom have increasingly become more frequent in several regions in Indonesia which have caused conflicts between communities. The problem discussed in this research is how the state's responsibility in guaranteeing religious freedom in Indonesia is viewed from the perspective of Human Rights (HAM). This research uses the normative juridical method. The conclusion of this research is that the Indonesian government guarantees that every citizen has the freedom to embrace his religion and carry out his worship in accordance with their respective beliefs. This is indicated by the existence of various legal products issued by the government to guarantee religious freedom in Indonesia. Various kinds of existing laws and regulations, apparently not followed by the implementation of law enforcement, so that in some regions in Indonesia there are still cases of intolerance where a group of minority religious adherents are prohibited from carrying out their worship by adherents of the majority religion.